Strategic Evaluation in Biopharma An adapted Balanced Scorecard for Late-Stage R&D Governance at AstraZeneca - Essunger, Hampus; Holm, Olle; Ladenvall, Adam; Farhad, Hanno; Kolovos, Raphael; Rutberg, Elias (My University, 2025)
The biopharmaceutical industry is characterized by long, uncertain and expensive R&D processes. Investment decisions in late-stage R&D projects, which often involve financial projections and strategic judgments, are therefore critical for companies’ success. The aim of this thesis has been to develop an adapted Balanced Scorecard specifically tailored for evaluating late-stage R&D projects at AstraZeneca, one of the largest biopharmaceutical companies in the world. The study addresses the challenge of integrating both quantitative financial parameters and qualitative parameters, such as strategic and competitive insights, into a comprehensive framework relevant for evaluating R&D projects. Through combining a theoretical framework through a systematic literature review on project evaluation methods in the biopharmaceutical industry, with a case study of AstraZeneca’s R&D evaluation process in the late-stage governance, based on interviews with relevant employees at the company and quantitative data from 12 projects, the study identifies and validates important evaluation parameters essential for R&D decision making in the biopharmaceutical sector. Some example parameters include metrics such as Net Present Value (NPV), Probability of Technical and Regulatory Success (PTRS), Portfolio Gaps within Resource Capabilities, and Product Area Dominance. These evaluation parameters have been synthesized into three overarching categories - Financial Impact, Strategic Fit and Competition, which when combined result in the AstraZeneca adapted Balanced Scorecard. The study finds that AstraZeneca in the past had difficulties integrating the Balanced Scorecard in their ways of working, due to its perceived complexity, and it was therefore phased out. To address these challenges, the adapted Balanced Scorecard presented in this thesis was developed to be simpler, more intuitive, and better aligned with AstraZeneca’s existing R&D evaluation practices. The simplification of the tool was achieved by including perspectives relevant to R&D project decision making and metrics already used by AstraZeneca. The study also presents and discusses in further detail how the adapted Balanced Scorecard is designed, discusses its application and what value it provides.
Keywords: Balanced Scorecard; R&D; Project Evaluation; Project Prioritization; Biopharma; AstraZeneca; Late-Stage Governance